The Statesman's Yearbook 2015
1588 p.
Keywords: Now in its 151st edition, The Statesman's Yearbook continues to be the reference work of choice for accurate and reliable information on every country in the world. Covering political, economic, social and cultural aspects, the Yearbook is also available online for subscribing institutions: Link